2011
DOI: 10.1103/physrevd.83.114025
|View full text |Cite
|
Sign up to set email alerts
|

Possible2Sand1Dcharmed and charmed-strange mesons

Abstract: Possible 2S and 1D excited D and D s states are studied, the charmed states Dð2550Þ 0 , D Ã ð2600Þ, Dð2750Þ 0 , and D Ã ð2760Þ newly observed by the BABAR Collaboration are analyzed. The masses of these states are explored within the Regge trajectory phenomenology, and the strong decay widths are computed within the heavy-quark effective theory. Both the mass and the decay width indicate that Dð2550Þ 0 is a good candidate for 2 1 S 0 . The strong decay property of D Ã ð2600Þ and D Ã s1 ð2700Þ AE is described w… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
81
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(88 citation statements)
references
References 50 publications
7
81
0
Order By: Relevance
“…[51], it was suggested that D * (2760) is a mixture of the 2 3 S 1 and 1 3 D 1 states, which is also supported by the study presented in Ref. [49]. However, calculation by the constituent quark model shows that the D (1 3 D 3 ) assignment of D * (2760) cannot be excluded [52], which is also supported by the works in Refs.…”
Section: Status Of the Observed Charmed Mesonssupporting
confidence: 70%
See 1 more Smart Citation
“…[51], it was suggested that D * (2760) is a mixture of the 2 3 S 1 and 1 3 D 1 states, which is also supported by the study presented in Ref. [49]. However, calculation by the constituent quark model shows that the D (1 3 D 3 ) assignment of D * (2760) cannot be excluded [52], which is also supported by the works in Refs.…”
Section: Status Of the Observed Charmed Mesonssupporting
confidence: 70%
“…In addition, the theoretical studies presented in Refs. [49,50] also show that D(2550) can be D(2 1 S 0 ), the first radial excitation of D mesons. However, the authors in Ref.…”
Section: Status Of the Observed Charmed Mesonsmentioning
confidence: 99%
“…According to the PDG [4], the low-mass charmed mesons D(1 1 for these observed charmed states have been studied in the context of various models such as the chiral quark model [5][6][7], the heavy meson effective theory [8][9][10], and the 3 P 0 model with the simple harmonic oscillator wave functions [11][12][13][14][15] or the nonrelativistic quark model wave functions [16], and other approaches [17][18][19]. It is also natural and necessary to exhaust the possible qq descriptions before restoring to more exotic assignments.…”
mentioning
confidence: 99%
“…As suggested in Ref. [20], a natural parity D sJ (2850) close to D * sJ (2860) may exist. However, no charmed strange resonance located around 2860 MeV with natural parity has been observed.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…D (2750) is possibly a 1 1 D 2 or a 1 3 D 2 state, it is also possibly an admixture of them [15,16,[18][19][20]. In any assignment, D(2750) can be observed in D(2750)π channel from hadronic decays of the four excited 2D states.…”
Section: D(2750)mentioning
confidence: 99%